2012
DOI: 10.1002/hup.2269
|View full text |Cite
|
Sign up to set email alerts
|

The loudness dependence of auditory evoked potentials and effects of psychopathology and psychopharmacotherapy in psychiatric inpatients

Abstract: The LDAEP in patients is related to severity of psychopathologic syndromes irrespective of diagnosis. Chronic psychopharmacologic treatment may also differentially modulate the LDAEP, but longitudinal studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 54 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…Since then, the role that NMDA receptors play in LTP was found to extend outside of the hippocampus to anatomically early areas within the visual (Artola and Singer, 1987;Kirk et al, 2010) and auditory cortices (Kirk et al, 2010) using paradigms that include rapid, repetitive presentations of sensory stimuli (e.g., flashing visual checkerboards, trains of auditory tones). In addition, several studies have demonstrated reduced LTP in the visual and auditory cortices of individuals with mood disorders (Normann et al, 2007;Ostermann et al, 2012;Yeap et al, 2009). Taken together, these studies suggest that up-regulation of LTP via ketamine administration might serve as an important mechanistic process mediating ketamine's antidepressant effects.…”
Section: Ketamine and Long-term Potentiationmentioning
confidence: 99%
“…Since then, the role that NMDA receptors play in LTP was found to extend outside of the hippocampus to anatomically early areas within the visual (Artola and Singer, 1987;Kirk et al, 2010) and auditory cortices (Kirk et al, 2010) using paradigms that include rapid, repetitive presentations of sensory stimuli (e.g., flashing visual checkerboards, trains of auditory tones). In addition, several studies have demonstrated reduced LTP in the visual and auditory cortices of individuals with mood disorders (Normann et al, 2007;Ostermann et al, 2012;Yeap et al, 2009). Taken together, these studies suggest that up-regulation of LTP via ketamine administration might serve as an important mechanistic process mediating ketamine's antidepressant effects.…”
Section: Ketamine and Long-term Potentiationmentioning
confidence: 99%
“…On the other hand, studies in patients taking GABAerge medication show that they have both lower LDAEP levels (measured at Cz) (Ostermann et al, 2012) and cortical GABA levels measured by MRS after administration (Goddard et al, 2004). These results are limited to the occipital cortex, as this area was preferably examined for increased measurement quality.…”
Section: Discussionmentioning
confidence: 99%
“…The N1/P2 amplitude was then calculated as the difference of peak amplitudes between N1 and P2. The LDAEP of the scalp data (Cz) was calculated as a median exponential slope of the amplitudes of the single loudness levels, since this method can be regarded as most validated measure for the LDAEP after 30 years of research in this field [Hegerl and Juckel, ; Ostermann et al, ].…”
Section: Methodsmentioning
confidence: 99%